2022
DOI: 10.2340/actadv.v102.1057
|View full text |Cite
|
Sign up to set email alerts
|

Ablative Fractional Laser-assisted Low-irradiance Photodynamic Therapy for Treatment of Actinic Keratoses in Organ Transplant Recipients: A Prospective, Randomized, Intraindividual Controlled Trial

Abstract: Pain and inferior efficacy are major limiting factors of conventional photodynamic therapy for the field treatment of actinic keratoses in immunosuppressed organ transplant recipients. This prospective randomized controlled study evaluates the efficacy and tolerability of ablative fractional laser system pretreatment combined with low-irradiance photodynamic therapy (18.5 mW/cm2) compared with conventional photodynamic therapy (61.67 mW/cm2) in the treatment of actinic keratoses on the face and scalp in organ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…When comparing online recruitment to traditional offline recruitment strategies, online strategies appear more time-efficient. Our review of the published literature on AK from the past 10 years highlighted the time efficiency of an online recruitment approach for RCTs in dermato-oncology ( Table 2 ) [ [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] ]. A review by Jacques RM et al of the recruitment rates using conventional strategies in 388 RCTs between 1997 and 2020 found that the median patient recruitment rate per site was 0.95 per month (0.03 per day) [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…When comparing online recruitment to traditional offline recruitment strategies, online strategies appear more time-efficient. Our review of the published literature on AK from the past 10 years highlighted the time efficiency of an online recruitment approach for RCTs in dermato-oncology ( Table 2 ) [ [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] ]. A review by Jacques RM et al of the recruitment rates using conventional strategies in 388 RCTs between 1997 and 2020 found that the median patient recruitment rate per site was 0.95 per month (0.03 per day) [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…49,50 Low-irradiance PDT combined with Er:YAG pretreatment achieved a significantly superior lesion response rate (mean ± standard deviation 77.3 ± 23.6%) compared with conventional PDT (61.8 ± 21.4%; p = 0.025) in intraindividual fields at 3 months without negatively impacting pain (p = 0.777) or cosmetic outcome (p = 0.157). 49 Photodynamic therapy has been combined effectively with other topical agents for field-directed therapy of AKs. Topical calcipotriol (a vitamin D analogue) twice daily for 2 weeks before AFL-assisted PDT was more effective than a placebo cream before AFL-assisted PDT in treating AK, particularly for thick-layered, moderate-to-severe AK lesions, in subjects of FPT III-V. 51…”
Section: Photodynamic Therapymentioning
confidence: 98%
“…Ablative fractional laser‐assisted low‐irradiance PDT (18.5 mW/cm 2 ) is more effective than conventional MAL‐PDT (61.67 mW/cm 2 ) for the treatment of AK on the face and scalp in organ transplant recipients, using a red light‐emitting diode lamp at a total light dose of 37 J/cm 2 49,50 . Low‐irradiance PDT combined with Er:YAG pretreatment achieved a significantly superior lesion response rate (mean ± standard deviation 77.3 ± 23.6%) compared with conventional PDT (61.8 ± 21.4%; p = 0.025) in intra‐individual fields at 3 months without negatively impacting pain ( p = 0.777) or cosmetic outcome ( p = 0.157) 49 …”
Section: Part 1: Non‐surgical Proceduresmentioning
confidence: 98%